AMOEBOID OLIVINE AGGREGATES WITH LOW-CA PYROXENES: A GENETIC LINK BETWEEN REFRACTORY INCLUSIONS AND CHONDRULES? - Krot A.N.; Petaev M.I.; Yurimoto H. (My University, 2004)
Amoeboid olivine aggregates (AOAs) in primitive (unmetamorphosed and unaltered) carbonaceous chondrites are uniformly 16 O-enriched (Δ17O - ~20‰) and consist of forsterite (Fa2), FeNi-metal, and a refractory component (individual CAIs and fine-grained minerals interspersed with forsterite grains) composed of Al-diopside, anorthite, ±spinel, and exceptionally rare melilite (Ak15 ); some CAIs in AOAs have compact, igneous textures. Melilite in AOAs is replaced by a fine-grained mixture of spinel, Al-diopside, and anorthite. Spinel is corroded by anorthite or by Al-diopside. In ~10% of > 500 AOAs studied in the CR, CV, CM, CO, CH, CB, and ungrouped carbonaceous chondrites Acfer 094, Adelaide, and LEW85332, forsterite is replaced to a various degree by low-Ca pyroxene. There are three major textural occurrences of low-Ca pyroxene in AOAs: (i) thin (<10μm) discontinuous layers around forsterite grains or along forsterite grain boundaries in AOA peripheries; (ii) haloes and subhedral grains around FeNi-metal nodules in AOA peripheries, and (iii) thick (up to 70μm) continuous layers with abundant tiny inclusions of FeNi-metal grains around AOAs. AOAs with low-Ca pyroxene appear to have experienced melting of various degrees. In the most extensively melted AOA in the CV chondrite Leoville, only spinel grains are relict; forsterite, anorthite and Al-diopside were melted. This AOA has an igneous rim of low-Ca pyroxene with abundant FeNi-metal nodules and is texturally similar to Type I chondrules.
Keywords: chondrite